3 UNJUK KERJA PROFESIONALISME KONSELOR MELALUI FAKTOR-FAKTOR NON-KOGNITIF SISWA - Widyarto, Wikan Galuh (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2016)
ABSTRACT The aim of research to empirically examine the factors of non-cognitive include: self-control ability, coping with anxiety, time management skill, problem solving skill, and academic achievement of student’s SMAN Malang. Data were collected using self-inventory self-control ability, coping with anxiety, time management skill, problem solving skill, and grades in Mathematics, Physics, Chemistry, and Biology, then analyzed by Spearman correlation. These samples included 224 students that high school students Pola Lima, drawn using multistage random sampling technique. Findings of this study are (1) Self-control ability, time management skills, coping with anxiety has a significant relationship to student achievement; (2) self-control ability themselves have a significant relationship with time management skills, coping with anxiety, problem solving positively oriented, rational problem-solving style, and avoidance problem solving style. Key words: Self-control ability, coping with anxiety, time management skill, and academic achievement.